Omicron the New COVID-19 Variant, a Review - Abdallh, Mustafa; A. Husain, Amani; Salman, Israa; Raheem, Rasha; Hairunisa, Nany; Amalia, Husnun; Alsayed, Raghda; Mohammed, Randa; Yousif, Emad (Al-Nahrain Journal of Science, 2022)
SARS-CoV-2 virus (COVID-19), the cause of coronavirus disease, has several variations. Some are thought to be particularly important or have been said to be so, because of their potential for greater transmissibility, Virus pathogenicity has grown, or vaccinations against them have become less effective. These mutations have a role in the COVID-19 pandemic's persistence.The B.1.1.529-Omicron variant, found in many coronavirus cases reported in South Africa discovered late 2021, having a surprisingly great number of mutations which raise a concern toward the spreadablity of this variant and severity of illness in comparison to other corona virus variants as well as the effectivity of the available vaccinations. This review summarizes of the most recent information and the answers to most of the world's questions about Omicron.